West African Economic and Monetary Union (WAEMU) : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper reviews West African Economic and Monetary Union's (WAEMU) regional macroeconomic surveillance framework to control all sources of debt accumulation and ensure debt sustainability. WAEMU's regional surveillance framework aims at ensuring the sustainability of national fiscal policies and their consistency with the common monetary policy. While fiscal deficits have been the main driver of public debt across WAEMU member countries, the size of residual factors has varied greatly among these countries. The WAEMU Macroeconomic Surveillance Framework would benefit from adjustments to more effectively set the region's public debt on a sustainable path. In addition, beyond adhering to the WAEMU fiscal deficit rule, member countries must curb below-the-budget-line operations. This would require improved monitoring of fiscal risks and the building of adequate budget provisions to address such risks before they materialize. Improved Treasury practices would also help eliminate the recourse to pre-financing arrangements and tighten control over expenditure. Public dissemination of the WAEMU progress report and strengthened peer-to-peer learning among member countries could improve the momentum for reforms.